Pengaruh Non Performing Loan Dan Loan to Deposit Ratio Terhadap Rerurn On Assets Pada PT. Bank Rakyat Indonesia (Persero) Tbk. - Risma; Afriyani; Andriani Yasin, Nurfatwa; Rahman, Agussalim (LPPM STIE Tri Dharma Nusantara - Makassar, 2025)
The purpose of this study is to determine the Effect of Non Performing Loan and Loan to Deposit Ratio on Return On Asset in PT. Bank Rakyat Indonesia (Persero), Tbk. The types of data used in this study are qualitative and quantitative. The data source used in this study is secondary data. The analysis methods used are descriptive analysis and multiple linear regression, determination coefficient (R2), correlation coefficient (r), t-test, and F test. The results of this study show the regression equation Y = 15,081 – 0.832X1 – 0.118X2, determination coefficient, (R2) = 31,2% and correlation coefficient (R) = 0,559. Non Performing Loan and Loan to Deposit Ratio have a significant effect on Return On Asset. Non Performing Loan have a negative and significant effect on Return On Assets. Meanwhile, the Loan to Deposit Ratio has a negative and significant effect on the Return On Asset at PT. Bank Rakyat Indonesia (Persero), Tbk. H1, H2 and H3 were rejected.